2006
DOI: 10.1016/j.physletb.2006.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Chromomagnetic stability of the three flavor Larkin–Ovchinnikov–Fulde–Ferrell phase of QCD

Abstract: We compute in the Ginzburg-Landau approximation the gluon Meissner masses for the LarkinOvchinnikov-Fulde-Ferrell (LOFF) phase of QCD with three flavors in the kinematical range where it is energetically favored. We find real Meissner masses and therefore chromomagnetic stability.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 54 publications
2
49
0
Order By: Relevance
“…In the g2SC case with κ 33 < 0 a non-coloured (α = 0) FFLO state may be enough to cure the chromomagnetic instability [230] (see also [231] for results in opposition), but it is a subtle problem if the non-coloured FFLO can stabilize in all colour channels of gluons for 3-flavour quark matter [232]. Generally the instability analysis tells us a tendency towards the destination at best, but cannot go into the ground state.…”
Section: Implications From Chromomagnetic Instabilitymentioning
confidence: 99%
“…In the g2SC case with κ 33 < 0 a non-coloured (α = 0) FFLO state may be enough to cure the chromomagnetic instability [230] (see also [231] for results in opposition), but it is a subtle problem if the non-coloured FFLO can stabilize in all colour channels of gluons for 3-flavour quark matter [232]. Generally the instability analysis tells us a tendency towards the destination at best, but cannot go into the ground state.…”
Section: Implications From Chromomagnetic Instabilitymentioning
confidence: 99%
“…As in (40), in each term the flavor indices j and k (or just k) that are not summed over are understood to differ from each other and from the summed indices I (or I and J).…”
Section: The Ginzburg-landau Approximation: Derivationmentioning
confidence: 99%
“…It seems likely, therefore, that a ground state with counter-propagating currents is required. This could take the form of a crystalline color superconductor [30,31,32,33,34,35,36,37,38,39,40,41] -the QCD analogue of a form of non-BCS pairing first considered by Larkin, Ovchinnikov, Fulde and Ferrell [42]. Or, given that the CFL phase itself is likely augmented by kaon condensation [43,44], it could take the form of a phase in which a CFL kaon condensate carries a current in one direction balanced by a counter-propagating current in the opposite direction carried by gapless quark quasiparticles [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand the color gauge group is spontaneously broken, which gives masses to the eight gluons [34]. We therefore expect nine NGB due to spontaneous breaking of the axial group SU (3) and U (1) V .…”
Section: Goldstone Modesmentioning
confidence: 99%
“…This means that the screening masses of some of the gluons are imaginary. On the other hand, it has been shown that this instability can be cured either by the crystalline color superconductivity [33,34,35,36] or by gluon condensed phases [37], as well as condensed meson current states [38].…”
Section: Introductionmentioning
confidence: 99%